Detection of atmospheric 15NO2 in the ν3 spectral region (6.3 μm). (March 2015) - Perrin, Agnes; Toon, Geoffrey; Orphal, Johannes
Abstract: A reinvestigation of the ν3 band of 15 NO2 has been performed using experimental data acquired in 2000 [Orphal J, Perrin A, Flaud JM, Smirnov M, Himmelmann, Voigt S, Burrows JP. J Mol Spec 2000;204:72–9]. The linelist generated in this way during this study was used to detect this isotopologue in the atmosphere for the first time, using balloon-borne solar occultation spectra measured by the JPL MkIV Fourier transform spectrometer. It is shown that over the 15–35 km altitude range where 15 NO2 can be detected, the retrieved 15/14 NO2 ratio is within 5% of the expected value (0.00364), implying that the absolute line intensities in the new linelist are accurate. Over the same altitude range the RMS spectral fitting residuals reduce significantly as a result of including the new 15 NO2 linelist, improving the accuracy of retrievals of all gases that absorb in the 1550–1650 cm −1 region (e.g., 14 NO2, H2 O, HDO, O2 ).